Physical and mechanical properties of Tenun Pahang fabrics using alternative yarns / Engku Liyana Zafirah Engku Mohd Suhaimi … [et al.] - Engku Mohd Suhaimi, Engku Liyana Zafirah (Penerbit UiTM (UiTM Press), 2016)
An investigation on the properties of Tenun Pahang fabric performances using alternative yarns was conducted. The studies were made in order to evaluate whether the Tenun Pahang fabric could be produced economically and at the same time maintain the fabric quality. Traditional Tenun Pahang fabric uses silk for both warp and weft. For this project, two alternative yarns were used which were bamboo and modal which were a little lower in cost compared to silk. These yarns were woven with two variations, one with the yarns as weft only while maintaining the silk warp and the other with both warp and weft using the alternative yarns. Four (4) physical testings and three (3) mechanical testings conducted on the fabric samples. The fabric samples were evaluated including weight, thickness, thread density, crease recovery angle, stiffness and drapability. The results show that modal/silk and bamboo silk fabrics are comparable in terms of stiffness and drapability, hence they have the potential to replace 100% silk Tenun Pahang.